Is the Host Viral Response and the Immunogenicity of Vaccines Altered in Pregnancy? - Zainab Saeed; Orene Greer; Nishel Mohan Shah (Antibodies, 2020)
The intricacy of the maternal immune system arises from its ability to prevent a maternal immune response against a semi-allogenic fetus, while protecting the mother against harmful pathogens. However, these immunological adaptations may also make pregnant women vulnerable to developing adverse complications from respiratory viral infections. While the influenza and SARS pandemics support this theory, there is less certainty regarding the clinical impact of SARS-CoV-2 in pregnancy. In the current COVID-19 pandemic, vaccine development is key to public preventative strategies. Whilst most viral vaccines are able to induce a seroprotective antibody response, in some high-risk individuals this may not correlate with clinical protection. Some studies have shown that factors such as age, gender, and chronic illnesses can reduce their effectiveness and in this review, we discuss how pregnancy may affect the efficacy and immunogenicity of vaccines. We present literature to support the hypothesis that pregnant women are more susceptible to respiratory viral infections and may not respond to vaccines as effectively. In particular, we focus on the clinical implications of important respiratory viral infections such as influenza during pregnancy, and the pregnancy induced alterations in important leukocytes such as TFH, cTFH and B cells, which play an important role in generating long-lasting and high-affinity antibodies. Finally, we review how this may affect the efficacy of vaccines against influenza in pregnancy and highlight areas that require further research.